'The Dark Millions in the Colonies are Unavenged': Anti-Fascism and Anti-Imperialism in the 1930s. (14th October 2016) - BUCHANAN, TOM
Abstract : The quotation in this title expresses a dilemma, as the 'dark millions' were likely to remain 'unavenged' so long as authors were asked to take sides on the Spanish Civil War rather than colonial oppression. Indeed, anti-fascism might well be thought of as, in a sense, antithetical to anti-imperialism. This article explores the relationship between anti-fascism and anti-imperialism, focusing on Britain and France. The first part looks at anti-imperialism in the era of the Popular Front; the second looks at how the tensions between anti-fascism and anti-imperialism were played out in the case of the major conflicts of the later 1930s in Abyssinia, Spain and China; the third discusses the imperialist assumptions of many anti-fascists. The article concludes by looking at the early phase of the Second World War.